Productivity of several upland rice under aluminum stress in acid dry land east lampung regency - Priyadi Priyadi; Rianida Taisa; Dulbari Dulbari; Rizky Rahmadi; Fajar Rochman (UNIVED Press, Dehasen University Bengkulu, 2023)
Aluminum stress is a limiting factor for crop production on acid dry land with a low pH. The objectives of this study were to obtain aluminum-tolerant upland rice varieties in acid dry land. The study was carried out using a completely randomized block design (RCBD) consisting of 8 varieties, namely IR64, Inpago 7, Dodokan, Situ Bagendit, Dod-Pup1, Situ Bg-Pup1, Batur-Pup1, Batur and 4 strains, namely 19 (PB5)-2, 20 (PB8)-1, 21 (PB15)-1, and 22 (PB16)-1. The results also showed that the Situ Bagendit variety with the Pup-1 locus gave the highest yield per plot compared to other varieties and lines, namely 287.5 g. These results also correlate with the ability of the variety to withstand aluminum stress, with a tolerance value of 3.00 (quite tolerant).